Peran Self-Efficacy Dalam Memediasi Pengaruh Entrepreneurial Mindset Terhadap Keputusan Berwirausaha Generasi Z - Dewi Qomariah Imelda; Sarah Putri Suwandi; Ika Niswatin Budiarti (Journal of Innovation Research and Knowledge, 2026)
The high unemployment rate among the productive-age population highlights the importance of entrepreneurship as a strategic approach to creating new employment opportunities. Generation Z, characterized by its adaptability to technological advancements and digital innovation, possesses significant potential to become entrepreneurs. However, entrepreneurial decision-making is influenced by various psychological factors, particularly entrepreneurial mindset and self-efficacy. This study aims to examine the effect of entrepreneurial mindset on entrepreneurial decision-making among Generation Z in Tanjung Selor, with self-efficacy serving as a mediating variable. The study employed a quantitative approach using an explanatory research design. Primary data were collected through questionnaires distributed to 100 Generation Z respondents selected using probability sampling techniques in Tanjung Selor District. Data were analyzed using Structural Equation Modeling (SEM) with AMOS 24 and SPSS 23 software. The findings indicate that entrepreneurial mindset has a positive and significant effect on both self-efficacy and entrepreneurial decision-making. Furthermore, self-efficacy has a positive and significant influence on entrepreneurial decision-making and acts as a mediating variable in the relationship between entrepreneurial mindset and entrepreneurial decision-making. These findings suggest that strengthening entrepreneurial mindset accompanied by increased self-efficacy can encourage Generation Z to make entrepreneurial career decisions with greater confidence. This study contributes both theoretically and practically by emphasizing the importance of developing entrepreneurial mindset and self-efficacy through entrepreneurship education and training programs to foster the growth of young entrepreneurs at the regional level.